2023
DOI: 10.1177/23969873221150022
|View full text |Cite
|
Sign up to set email alerts
|

European Stroke Organisation (ESO) expedited recommendation on tenecteplase for acute ischaemic stroke

Abstract: Within the last year, four randomised-controlled clinical trials (RCTs) have been published comparing intravenous thrombolysis (IVT) with tenecteplase and alteplase in acute ischaemic stroke (AIS) patients with a non-inferiority design for three of them. An expedited recommendation process was initiated by the European Stroke Organisation (ESO) and conducted according to ESO standard operating procedure based on the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) framework. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 60 publications
(171 reference statements)
0
35
0
6
Order By: Relevance
“…Преимущества технологии ВТ при помощи болюсного тромболитика привели к постепенному переходу некоторых центров на повсеместное использование тенектеплазы, что позволило не только существенно снизить показатель времени «от двери до иглы», но и улучшить функциональные исходы инсульта [16][17][18]. В результате в 2023 г. Европейское общество инсульта в рекомендательном документе указало на возможность и преимущества ВТ тенектеплазой у всех пациентов в первые 4,5 ч инсульта [5].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Преимущества технологии ВТ при помощи болюсного тромболитика привели к постепенному переходу некоторых центров на повсеместное использование тенектеплазы, что позволило не только существенно снизить показатель времени «от двери до иглы», но и улучшить функциональные исходы инсульта [16][17][18]. В результате в 2023 г. Европейское общество инсульта в рекомендательном документе указало на возможность и преимущества ВТ тенектеплазой у всех пациентов в первые 4,5 ч инсульта [5].…”
Section: Discussionunclassified
“…не отличалась, а число серьезных нежелательных явлений было статистически достоверно ниже в группе неиммуногенной стафилокиназы (p = 0,044) [19,20]. Преимущество неиммуногенной стафилокиназы перед тенектеплазой заключается в том, что первая не требует учета массы тела пациента, тогда как вторая должна вводиться в дозе 0,25 мг/кг, что требует взвешивания пациента перед началом терапии [5]. В настоящем исследовании масса тела пациентов варьировала до 55 до 140 кг.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As tenecteplase is easier to prepare and administer than alteplase, our opinion is that it should be considered a first-hand choice. During revision of this article the European Stroke Organisation published revised recommendations on stroke thrombolysis, now recommending tenecteplase 0.25 mg/kg as a safe and effective alternative to alteplase 0.9 mg/kg (Alamowitch et al, 2023). Unfortunately, the COVID-19 pandemic stopped access to tenecteplase.…”
Section: Discussionmentioning
confidence: 99%
“…6 Currently, the European Stroke Organisation has recommended IVT with tenecteplase 0.25 mg/kg for LVO patients who are candidates for EVT and tenecteplase 0.25 mg/kg as a safe and effectiveness alternative to alteplase 0.9 mg/kg for all AIS patients eligible for IVT within 4.5 h from stroke onset. 7 The recent AcT trial showed that tenecteplase was non-inferior to alteplase in all AIS patients who meet the standard criteria for IVT. 8 With a similar safety profile, improved early recanalization rates, 9 and single bolus administration, tenecteplase may be an economic alternative to alteplase for AIS patients.…”
Section: Introductionmentioning
confidence: 99%